PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN PERMAINAN LENTUR UNTUK MENINGKATKAN ANTUSIAS DAN PRESTASI BELAJAR SISWA KELAS 5 SDN 01 PUNTEN - Mifta Irene Nabila; Arina Restian; Ernaz Siswanto (CV. ADIBA AISHA AMIRA, 2024)
The science and science subject is one of the subjects that is considered difficult by some students, including class V students at SD Negeri 01 Punten. Low student learning outcomes are caused by students' low enthusiasm for learning. If a passive response during learning continues, it makes students lazy in learning and students' thinking power becomes less sharpened. One effort to increase enthusiasm for learning is by using the PBL learning model assisted by Flexible Games (puzzle adventure). This research aims to describe the steps for PBL learning and the magnitude of the increase in enthusiasm and learning achievement of class V students at SD Negeri 01 Punten. The type of research used is Classroom Action Research (PTK). The research location is at SD Negeri 01 Punten. The research subjects were 22 students in class V A. The model used is qualitative. The data collected consists of numbers and descriptive sentences, and is analyzed thoroughly. Based on the results of the research and discussion, it was concluded that the PBL model assisted by the Flexible Game (Puzzle Adventure) can increase student enthusiasm and learning achievement. Proven by the results of the enthusiasm for learning questionnaire, 95% agreed, where the percentage results are classified as very high. Increased learning achievement can be seen from student learning completeness. In cycle I, learning completeness was 70%, while in cycle II it was 80%, where students had achieved classical completeness.